Fair and Equitable Grading for ALL Students in Inclusive Settings. Issue 4 (November 2022) - Wakeman, Shawnee Y.; Thurlow, Martha; Reyes, Elizabeth; Kearns, Jacqueline
Grading is a common practice in general education settings. Few teachers, however, are clear about how they should grade students with significant cognitive disabilities when those students are included in the general education classroom. Unfortunately, existing research provides minimal information to aid teachers and education leaders as they consider fair and equitable grading practices for these students. In this article, we examine the four criteria for high-quality inclusive grading outlined by The William & Mary Training & Technical Assistance Center for grading within the inclusive classroom: (a) grades are accurate, (b) grades are meaningful, (c) grades are consistent, and (d) grades are supportive of learning and discuss how these criteria could be applied to provide a more fair and equitable grading system for students with significant cognitive disabilities.